Member of the Scientific Committee - Kyranou, Maria (My University, 2026)
The annual conference of the HNA is a recurring event which could not be performed with physical attendance due to the Covid pandemic. The scientific committee took on the role of contacting presenters and guiding them through their submission for online attendance and presentation. The online event was very successful with more than 500 nurses attending.